2023
DOI: 10.1038/s41467-023-36084-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid metabolic reprogramming mediated by the AMP-activated protein kinase during the lytic cycle of Toxoplasma gondii

Abstract: The ubiquitous pathogen Toxoplasma gondii has a complex lifestyle with different metabolic activities at different stages that are intimately linked to the parasitic environments. Here we identified the eukaryotic regulator of cellular homeostasis AMP-activated protein kinase (AMPK) in Toxoplasma and discovered its role in metabolic programming during parasite’s lytic cycle. The catalytic subunit AMPKα is quickly phosphorylated after the release of intracellular parasites to extracellular environments, driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…We observed 1197 transcripts with higher abundance in parasites cultured in low iron conditions compared to untreated parasites, whilst just 44 were downregulated (log 2 fold change £-2, adjusted p -value (padj) < 0.05) ( Table S1 ). This bias towards upregulation of transcripts was unexpected and was not seen upon oxidative stress induction (Augusto, 2021) or upon downregulation of an essential metabolic regulator (Li et al ., 2023).…”
Section: Resultsmentioning
confidence: 96%
“…We observed 1197 transcripts with higher abundance in parasites cultured in low iron conditions compared to untreated parasites, whilst just 44 were downregulated (log 2 fold change £-2, adjusted p -value (padj) < 0.05) ( Table S1 ). This bias towards upregulation of transcripts was unexpected and was not seen upon oxidative stress induction (Augusto, 2021) or upon downregulation of an essential metabolic regulator (Li et al ., 2023).…”
Section: Resultsmentioning
confidence: 96%
“…Our previous results showed that the kinase domains of Tg KIN and Tg AMPKα have significant sequence similarities, with 51% and 72% amino acid sequence identity and similarity respectively (Li et al., 2023 ). Outside the kinase domains, the two proteins share little similarities (Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Plaque, two‐colour invasion, replication, and bradyzoite induction experiments were performed as described previously (Li et al., 2023 ; Xia et al., 2018 ; Yang, Yin, et al., 2022 ). All strains were pretreated with or without rapamycin for 48 h to induce the excision of floxed AMPKα before phenotypic assessment, as indicated in figure legends.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations